Nucleophilic Trapping of Alkoxy-Stabilized Oxyallyl Systems Generated from Inosose 2-O-Mesylates - Stockton, Kieran P.; Glover, Stephen A.; Greatrex, Ben W. (Synlett, 2015)
Protected inosose 2-O-mesylates generate oxyallyl systems by elimination of the mesylate group after enolization. The reaction is promoted by weak bases such as triethylamine and azide, and the oxyallyl systems are then trapped by nucleophilic alcohols or azide. Computations using DFT/B3LYP confirm that the singlet planar oxyallyl is stabilized by the exocyclic alkoxy group.
Keywords: nucleophilic addition; carbocycle; carbohydrates; rearrangement; carbocation